Designing English materials promoting HOTS for senior high school students of the science study program - Wulandari, Lutfina Tarita; Widyantoro, Agus (LingTera, 2021)
This study aimed to develop English supplementary reading materials promoting HOTS for senior high school students majoring in the science study program. The procedures of conducting this study were the identification of needs, exploration of needs, contextual realization and pedagogical realization of materials, materials production, evaluation by the experts, student use of materials, and evaluation by the students. It was concluded that the appropriate supplementary textbook for the eleventh grade students majoring in the science study program was a textbook which promoted HOTS, followed the 2013 curriculum, and considered the students' needs. EXCELLENT, the textbook prototype developed in this study was considered appropriate for teaching and learning English since it met those criteria. It was proved by the results of the evaluation by the expert and students. The mean value of the expert judgement on the textbook quality was 4.71, which was classified into "very good" category. Meanwhile, the mean value of the students' evaluation on the textbook quality was 3.92 categorized as "good".